Control of Aerial Manipulators for Contact Inspection - Matosse, James (University of the Witwatersrand, Johannesburg, 2023)
Aerial manipulators are flying robotic systems that consist of a multi-rotor vehicle tailored with one or more manipulators. These systems are promising for contact inspection of chemical plants, boilers, tunnels and chimneys without human intervention. They require sophisticated control algorithms for control and stabilisation of complex varying dynamics due to the flying, manipulating and interacting with the environment. The dynamics of an aerial manipulator are treated as two subsystems, the quadrotor and the manipulator. The quadrotor dynamics are extracted through the Newton-Euler algorithm using quaternion-based orientation instead of Euler angles. The manipulator dynamics are extracted using the recursive Newton-Euler equations for purposes of handling the floating-base effect. A classic impedance control is a widely used effective control for contact force tracking but it requires the location of the environment relative to the end-effector and the environmental stiffness to be known precisely, and mostly- the desired force as a constant. In contact inspection without human intervention, the environmental properties (geometrical and mechanical) are uncertain, causing the classic impedance control method to be less effective. Presented in this study are: an adaptive variable impedance control (AVIC) for force tracking combined with the integral linear quadratic regulator (LQR) for the quadrotor and proportional-derivative (PD) for the manipulator’s navigation control. AVIC has the capability to counteract for environmental uncertainties by varying the impedance parameter (damping coefficient) on-line corresponding to the force tracking error. This control has been utilised effectively in industrial robot manipulators for a stable force tracking performance. So far in the literature, AVIC together with integral LQR and PD controllers have not been applied to aerial manipulators as a control strategy. Since the aerial manipulator is a coupled system, a linearisation process was performed on the quadrotor dynamics coupled with the manipulator to achieve a fair approximation of the non-linear model. This study has improved force tracking abilities through the implementation of AVIC that allows the aerial manipulator to achieve a desired contact force on the inspected contour while the quadrotor remains in a stable position. Finally, the developed system was simulated using MATLAB/SIMULINK program and the attained results proved the effectiveness of the strategy in comparison to the classic impedance control.
A research dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the Master of Science in Engineering, in the School of Mechanical, Industrial and Aeronautical Engineering, in 2023.
Keywords: Contact inspection; Integral LQR; Adaptive variable impedance control (AVIC) strategy; Computed torque control; Environmental uncertainty; Flying robotic systems; UCTD; SDG-9: Industry, innovation and infrastructure